The role of the principal as an instructional leader in improving learner achievement in township schools: a case study of two primary schools of Soweto in Gauteng province - Khumalo, Sithembile Lucas (My University, 2016)
This study explores the role of the principal as an instructional leader in two successful township primary schools in challenging circumstances. It examines instructional strategies used by principals of the two schools that may account for high levels of learner achievement and explores how these successful leaders deploy leadership styles and management approaches to deal with prevailing challenging circumstances that affect their schools academically and other spheres of governance and management. Sixteen participants were involved including 2 principals, 4 Heads of department (HODs), 4 educators, 4 parents from the two schools and 2 district officials under who both schools account. Using qualitative approaches, triangulation of data was achieved through semi-structured interviews, observation and document analysis. The study found that the key instructional leadership approaches used by these principals were promoting teamwork, active participation, collective decision making, sharing of responsibilities, collaboration/collegiality and distribution of tasks amongst multiple leaders or people. The claims made by the principals were corroborated by educators, parents, members of the School Management Team (SMT) and district management teams. Data also indicated that the principals relied on a combination of different leadership styles and efficient and effective management approaches with their subordinates to garner the enthusiastic implementation of instructional approaches which are claimed to yield good learner outcomes in Annual National Assessment (ANA) tests. The study suggests that there might be a strong link between leadership styles and management approaches on one hand and learner performance on the other. Further, the data suggests that the application of appropriate management systems and relevant leadership styles can contribute to institutional resilience against the prevailing challenges which tend to depress performance in many schools in similar circumstances. The findings of the study have several important implications including:  Schools as organisations require the collective effort of all stakeholders in order to achieve their objectives or goals.  That ‘one size fits all’ form of leadership has no place in different environments but that more often than not, a combination of different leadership styles and management approaches should be explored in an attempt to realize a common vision of an organisation. The study makes specific recommendations for a more broad based research agenda to examine factors which contribute to resilience and success in schools operating in challenging circumstances. It also calls for more contextualised studies in specific schools to explore the leadership forms that have greatest potential for delivering better learning outcomes in schools facing challenging circumstances.
Submitted in partial fulfilment for the degree of Masters in Education at the University of the Witwatersrand, Johannesburg, South Africa 30 June 2015
Keywords: Resilient schools; Leadership; Management; Instructional leadership; Learner outcomes